Leonid Dolgopolov’s Unpublished PhD Thesis on Alexander Blok’s Narrative Poems ‘Retribution’ and ‘The Twelve’ - Vassili Molodiakov (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2021)
Russian Modernism scholar Leonid Konstantinovich Dolgolopov (1928 –1995), known for his studies on Alexander Blok and Andrei Bely, completed his PhD thesis on Blok’s narrative poems “Retribution” and “The Twelve” in 1960, received his degree in 1962, but never published the text (now in the author’s possession). Its major parts were published as papers, its principal propositions and conclusions were developed in Dolgopolov’s later research works, but the thesis was never printed as a whole, and, from the author’s point of view, is worth being published as a valuable source for history of literary studies on Russian Symbolism as well as an original work useful and readable even now. The article presents Dolgopolov’s unpublished PhD thesis. Chapter One deals with “Retribution” and presents a comprehensive study of the poem’s plan, plot, and literary history, its genre peculiarities and historical scenes. Chapter Two analyzes evolution of Blok’s political views during the First World War and the Russian Revolution of 1917 and also its reflection in Blok’s lyric poems of this period. Chapter Three is the first of Dolgopolov’s numerous studies on “The Twelve”, the work he considered to be Blok’s highest literary achievement. Dolgopolov analyzed the poem’s ideas and images (especially Jesus Christ), its formal and rythmic novelty, its place among other contempopary poetical works on Russian revolution.